EFFECT OF SEED PRIMING TREATMENT ON SEED QUALITY PARAMETERS IN CUMIN (Cuminum cyminum) - KALYANRAO; SUDESHNA CHAKRABORTY; ANIL RAVAT AND VRUSHANK TRIVEDI (The Bioscan, 2021)
The present investigation deals with five varieties of cumin i.e., GC 1, GC 2, GC 3 and GC 4, collected from Centre for Research on Seed Spices, Sardarkrushinagar Dantiwada Agricultural University, Jagudan and var. RZ 209 was obtained from National Research Centre on seed Spice, Ajmer. All the five varieties were subjected to different priming treatments i.e. -1.2 MPa PEG, -0.8 Mpa, PEG, 0.1% KNO 3 and 0.2 % KNO 3 and control for two consecutive years. The data obtained from various observations were analyzed by using Factorial Completely Randomized Design (FCRD). The results revealed that there was significant effect of priming treatments and varieties on germination per cent and other seed quality parameters like seedling vigour index I and II.